IMPACT OF LEFT VENTRICULAR GEOMETRY, EXPRESSED AS INTERVENTRICULAR SEPTAL AND POSTERIOR WALL THICKNESS, ON THE OUTCOME OF ACUTE ISCHEMIC STROKE - Munjiza, Dejan; Georgievski-Brkić, Biljana; Vitošević, Filip; Dimitrijević, Ljubica; Vukićević , Marjana (Srpski medicinski časopis Lekarske komore, 2026)
Introduction/Objective: Acute stroke represents a significant component of the overall health burden of the population. Parameters obtained by transthoracic echocardiography are well-established predictors of outcomes in cardiovascular diseases, while increasing evidence indicates their importance in predicting outcomes in neurovascular disorders. This study aims to test the hypothesis that changes in left ventricular geometry, expressed as an increase in left ventricular wall thickness, represent a useful marker of poor outcome in patients with acute ischemic stroke. Materials and methods: The methodology was based on the analysis of echocardiographic variables in 167 patients with acute ischemic stroke, together with variables of the modified Rankin Scale assessed at hospital discharge, used as an indicator of functional outcome. Results: The study indicates a correlation between the thickness of both the interventricular septum and the posterior wall of the left ventricle, on the one hand, and the functional status of patients, on the other. The results confirmed the study hypothesis, demonstrating that an increase in interventricular septal thickness and/or posterior left ventricular wall thickness is associated with a higher probability of unfavorable outcome. Conclusion: Both evaluated echocardiographic parameters showed positive predictive value in relation to functional outcomes.